Effect of Single Acupuncture Point (Liver 7) on Pain and Range of Motion on Osteoarthritis of Knee - M. Periyachishreepriya; P. Kumaresan; A. Naveena; P. Prabu; M. Sendhilkumar (Medical Association of Pharmacopuncture Institute, 2024)
Background : Osteoarthritis of the knee (OAK) is a chronic degenerative musculoskeletal disorder that strongly affects the elderly population and decreases their quality of life. Pain, stiffness, and restricted knee movements are the major characteristic features of OAK. There are no studies available on the effect of the liver 7 (LR 7) acupuncture point on pain and range of motion. Objectives: To study the effectiveness of the LR 7 acupuncture point on pain and range of motion in chronic OAK patients. Methods : Thirty-five subjects aged between 40 and 65 years were recruited from Government Yoga and Naturopathy Medical College, Chennai. Participants were included in the study after they fulfilled the eligibility criteria. The duration of acupuncture was 20 minutes (5 days/week) for 2 weeks. Baseline and post-intervention assessments were performed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and the degree of knee flexion and extension was measured using a goniometer. Results : Pre- and post-trial outcomes were compared using paired t-tests. LR 7 acupuncture reduced the WOMAC score from 49 to 30 (p < 0.001), indicating that pain was alleviated. Treatment increased the range of knee flexion from 110 to 115 degrees and reduced knee extension (p < 0.01) from 16 to 9 degrees (p < 0.001). These findings indicate that acupuncture treatment improved the range of knee movement. Conclusion : The present study showed that 10 sessions of LR 7 acupuncture for people with OAK significantly reduced pain and increased range of motion. We conclude that LR 7 acupuncture is an adjuvant therapy for alleviating pain and managing OAK.